2020
DOI: 10.1002/eqe.3316
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of modal characteristics of a mid‐rise cold‐formed steel building during construction and earthquake testing

Abstract: Vibration-based structural identification is an essential technique for assessing structural conditions by inferring information from the dynamic characteristics of structures. However, the robustness of such techniques in monitoring

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…At last, few authors investigated the effects of non-structural components and equipment on the building dynamic [78] FVs (shaker) EDS Dhakal et al [79] AVTs Shell De Angelis and Pecce [80] AVTs EDS De Angelis and Pecce [81] AVTs EDS Asgarian and McClure [82] AVTs EDS and Shell Mora et al [83] AVTs EDS and Shell Pan et al [84] AVTs Shell Yun et al [85] AVTs EDS Zhou et al [86] AVTs EDS and Shell Su et al [87] AVTs Shell Aras [88] AVTs and ILTs (Hammer) Shell O'Reilly et al [89] AVTs and FVs (Earthquakes) EDS But and Omenzetter [90] FVs (Earthquakes) EDS behaviour. It is the case of Alembagheri et al [91], who dynamically tested a full-scale laboratory 3-D steel module with different gypsum-board walls, or Wang et al [92], who tested a full-scale steel structure specimen over a shaking table focusing also on the effects of interior partitions and plant piping. Also, Astroza et al [93] tested a full-scale RC specimen over a shaking table in different construction stages and, moreover, once non-structural components and equipment have been installed, in order to investigate the dynamic interaction between them and the structural members.…”
Section: Effects Of Infill Masonry Walls On the Dynamic Behaviour Of ...mentioning
confidence: 99%
“…At last, few authors investigated the effects of non-structural components and equipment on the building dynamic [78] FVs (shaker) EDS Dhakal et al [79] AVTs Shell De Angelis and Pecce [80] AVTs EDS De Angelis and Pecce [81] AVTs EDS Asgarian and McClure [82] AVTs EDS and Shell Mora et al [83] AVTs EDS and Shell Pan et al [84] AVTs Shell Yun et al [85] AVTs EDS Zhou et al [86] AVTs EDS and Shell Su et al [87] AVTs Shell Aras [88] AVTs and ILTs (Hammer) Shell O'Reilly et al [89] AVTs and FVs (Earthquakes) EDS But and Omenzetter [90] FVs (Earthquakes) EDS behaviour. It is the case of Alembagheri et al [91], who dynamically tested a full-scale laboratory 3-D steel module with different gypsum-board walls, or Wang et al [92], who tested a full-scale steel structure specimen over a shaking table focusing also on the effects of interior partitions and plant piping. Also, Astroza et al [93] tested a full-scale RC specimen over a shaking table in different construction stages and, moreover, once non-structural components and equipment have been installed, in order to investigate the dynamic interaction between them and the structural members.…”
Section: Effects Of Infill Masonry Walls On the Dynamic Behaviour Of ...mentioning
confidence: 99%
“…Regarding seismic behaviour and structural analysis, it is shown that LSF system in combination with shear walls can be considered as an appropriate choice in areas with high seismic hazards or high important buildings like schools and hospitals based on experimental researches of Fiorino, Iuorio, and Landolfo (2014), Iuorio, Fiorino, and Landolfo (2014), Khalifa et al (2020) and Wang and Hutchinson (2020).…”
Section: Lsf Systemsmentioning
confidence: 99%
“…These migrations have not only improved socioeconomic condition of local area but also provides an opportunity to multi-cultural society to develop complex building structures with newer construction material and techniques [2]. Local and central government have invested in upscaling human development in urban areas by providing physical infrastructures (landscape building, libraries, railways, roads, business parks, schools, electricity, and other day-to-day utilities) and critical infrastructure (hospital, military bases, emergency shelter) [15]. These public buildings and infrastructure were designed and construct with the resources available at the time of construction to fitful their long-term usability by withstanding extreme weather, capacity, and load.…”
Section: Background and Literature Reviewmentioning
confidence: 99%